Physiology: 700 questions and answers - David G Penny (Appleton and Lange, 1996)
the book offers a concise review for medical students preparing for physiologe courses and Board examinations. It reflects the increasing clinical knowledge in physiology and contains 700 multiple-choice, exam-type questions. Explanatory answers with updated references are provided for furthur study